THE USE OF AEGISUB IN TEACHING AUDIOVISUAL TRANSLATION CLASSES: A REVIEW ON IT-BASED SUBTITLING COURSE - Achmad Basari; Raden Arief Nugroho (Proceedings Education and Language International Conference, 2017)
The use of technology in subtitling practices reaches its peak nowadays. A number of tools have been used to maximize the quality of audiovisual/screen translation and to have the translation works done more efficiently. One of the tools is AEGISUB software. This software is popular among fansub translators as a free tool to help produce the desirable subtitles. This study reviews the use of AEGISUB software in a classroom project of subtitling course. By using the classroom observation method during the course, the researchers recorded and reviewed the applications of the software conducted by the students. Based on the observation, the students performed the intended procedures to create subtitles of the target text. By applying the software, the students learned well how to deal with technical shortage as well as linguistic barriers of verbal communication. Keywords: AEGISUB software, Subtitling